2005
DOI: 10.1002/jcb.20639
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinases p38 and JNK are activated by the steroid hormone 1α,25(OH)2‐vitamin D3 in the C2C12 muscle cell line

Abstract: In chick skeletal muscle cell primary cultures, we previously demonstrated that 1alpha,25(OH)2-vitamin D3 [1alpha,25(OH)2D3], the hormonally active form of vitamin D, increases the phosphorylation and activity of the extracellular signal-regulated mitogen-activated protein (MAP) kinase isoforms ERK1 and ERK2, their subsequent translocation to the nucleus and involvement in DNA synthesis stimulation. In this study, we show that other members of the MAP kinase superfamily are also activated by the hormone. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 68 publications
2
45
0
Order By: Relevance
“…Changes observed are not restricted to a particular pathway, perhaps as there is considerable interaction between secondary messenger cascades, both up and downstream (Bitar and Patil, 2004;Buitrago et al, 2006). Oxidative stress occurs early in the progression of Alzheimer disease, and may be the result of the activation of stress-activated protein kinase pathways (Zhu et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…Changes observed are not restricted to a particular pathway, perhaps as there is considerable interaction between secondary messenger cascades, both up and downstream (Bitar and Patil, 2004;Buitrago et al, 2006). Oxidative stress occurs early in the progression of Alzheimer disease, and may be the result of the activation of stress-activated protein kinase pathways (Zhu et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…The differentially expressed mRNAs encode proteins that play significant roles in multiple biochemical pathways involved in muscle contraction and relaxation; extracellular matrix-cell receptor interactions; actin cytoskeleton remodeling; and JAK-STAT, insulin-like (17) 0.014 Reactome p53 pathway (16) 0.014 Panther Interferon-signaling (11) 0.017 Panther Muscle contraction (9) 0.022 Reactome Terpenoid backbone biosynthesis (6) 0.028 KEGG Cell adhesion molecules (24) 0.048 KEGG (27), which showed that treatment of vitamin D-deficient humans with cholecalciferol improves muscle phosphocreatine recovery after exercise, suggesting an effect of 1␣,25(OH) 2 D 3 on the formation of high energy phosphorylated intermediates and mitochondrial function. The increase in the numbers of mitochondria could also account for the increase in cellular OCR.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we and others have shown that in HL60 cells ERK1/2 is activated in the early phase of 1,25D-induced differentiation, and this can be accentuated by serum starving the cells prior to exposure to 1,25D (Marcinkowska et al, 1997;Marcinkowska, 2001;Wang and Studzinski, 2001a). Other studies have implicated JNK (Ji et al, 2002;Wang et al, 2003;Buitrago et al, 2006), p38 (Wang and Studzinski, 2001a,b;Ji et al, 2002) and AKT (Zhang et al, 2006) pathways in the transmission of the 1,25D-generated signals to the transcriptional machinery in the nucleus. However, the Raf-MEK-ERK pathways remains firmly established as a principal all-purpose signaling cascade (Chang et al, 2003), and as such deserve additional attention regarding its role in the induction of differentiation.…”
mentioning
confidence: 90%
“…These findings support the thesis that Raf-1 signals cell proliferation and cell differentiation through different intermediary proteins Involvement of mitogen-activated protein kinases (MAPKs) in signaling of monocyte/ macrophage differentiation induced by 1,25-dihydroxyvitamin D 3 (1,25D) has been well documented (e.g., Wang et al, 2000;Marcinkowska, 2001;Wang and Studzinski, 2001a;Kim et al, 2002;Studzinski et al, 2005), but the exact sequence of signaling steps has not been precisely elucidated. Early studies described MAPK activity as the basis of rapid, membranerelated effects of 1,25D on human acute promyelocytic leukemia NB4 cells (Song et al, 1998) and other cell types (Buitrago et al, 2006). These effects occurred in the time frame of seconds and minutes, but have not been universally observed in other cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation